Development of cleaved amplified polymorphic sequence marker for powdery mildew resistance in Korean malting barley using QTL-seq - Park, Jin-Cheon; Yoon, Young-Mi; Lee, Chang-Hyun; Hur, On-Sook; Kim, Sang-Min (Frontiers in Plant Science, 2025)
IntroductionPowdery mildew (PM) caused by Blumeria graminis f.sp. hordei is a major fungal disease affecting barley (Hordeum vulgare L.). The most effective approach to controlling this disease is the development of resistant cultivars. In this study, we investigated the genomic regions associated with PM resistance by performing quantitative loci sequencing (QTL-seq) twice using the parental lines ‘Hopum’ (susceptible) and ‘Jeonju 182’ (resistant) as reference genomes.MethodsThis study was conducted from 2022 to 2024 at the National Institute of Agricultural Sciences in Wanju, Republic of Korea. We conducted artificial crossing, genomic DNA extraction, phenotypic evaluation, QTL-seq analysis, and cleaved amplified polymorphic sequence (CAPS) marker development. Candidate gene expression was analyzed using real-time quantitative reverse transcription PCR.ResultsA total of 2,130 common variants were identified in two regions of chromosome 1H (6,940,595–18,008,713 bp and 19,363,700–20,551,018 bp). Twenty-one non-synonymous single nucleotide polymorphisms among these variants were used to develop CAPS markers, which were validated in an F2 population and malting barley cultivars. The PMC_75 marker, which is annotated as HORVU.MOREX.r3.1HG0005790, showed a strong association with resistance and was highly expressed in ‘Jeonju 182.’ This marker is associated with a Clathrin Assembly Protein, which is involved in vesicle formation and intracellular trafficking, processes essential for cellular signaling and defense responses.ConclusionThe development of the CAPS marker (PMC_75) provides a valuable tool for marker-assisted selection in breeding PM-resistant malting barley, improving breeding efficiency, and accelerating the development of resistant cultivars.